Inference and reading comprehension in university students - Melgarejo, Teófilo Félix Valentín; Vivar, Pablo Lenin La Madrid; Pando, Clodoaldo Ramos; Melgarejo, Pablo Lolo Valentín; Adauto, Agustín Arturo Aguirre (Nurture, 2024)
Purpose: The objective of this research was to determine the relationship between inference and reading comprehension. We sought to verify the relationship between inductive and deductive inferences in the comprehensive reading of Daniel Alcides Carrión National University Peru students majoring in communication and literature. Design/Methodology/Approach: The correlational-explanatory research design was used since the correlation of the study variables was sought through scientific and specifically analytical, deductive and interpretive methodology on a population of 104 and the probabilistic sample of 83 students. Similarly, a 20-item questionnaire was used through survey, observation and recording techniques to collect the information. Therefore, the research was developed using a basic quantitative approach. Findings: The result of the study allowed us to obtain a correlation coefficient of 0.215 which was positive but moderate according to Spearman's Rho statistical statistician. Conclusion: The process of inductive and deductive inferences is related to the reading comprehension of university students. Therefore, reading strategies must be implemented in university training institutions to develop inferences in a relevant way. Practical Implications: The result of the study will allow university training centers to develop the inference process in the academic training of students. Contribution to the Literature: Information is contributed about the theoretical underpinnings of inference and reading comprehension in this study.